NARRATIVAS DE EXPERIÊNCIAS VIVIDAS POR DOCENTES E DISCENTES COM USO DE TECNOLOGIA DE INFORMAÇÃO E COMUNICAÇÃO – TDIC NA EDUCAÇÃO BÁSICA - LIMA, FABIANA ANHAS BARBOSA (2015)
We live in a period of political transformations, economic, social and cultural, all the time, in the imposing challenges. In this context, in recent decades, the use of technology has been extended in several everyday activities, dissemination of information, in the communication, as a means of expression and organization of society. The school, while social institution, needs to recognize this new reality, this different possibility of acquisition and processing of knowing, so that it can intervene, resign and redirect its action in order to meet the demands of its time. The general objective of this research, from the presentation and analysis of experiments with the use of information technologies and knowledge, reflect on how to put these tools in the process of teaching and learning in school from the view of teachers and students, aiming at the integral formation of the learner. In this way, development, understand each other as necessary to meet and consider the historical context, as well as school-related prospects and its protagonists (teachers and students) in the information and knowledge society. We emphasize the importance of teaching staff (training) and its role as a mediator in the process of learning, as well as receiving to technology, watching this performance space and function. We emphasize the use of TDIC experiments performed by teachers and students as the game production, scientific journals, writing stories, artistic productions, blogs, vlogs, discussions in groups present in social networks. The methodology used in this research is qualitative, action research mode and narrative, in function of the involvement with the Group and with the activities developed, in which participants share their personal stories with the researcher and learning related to actions or activities that perform, providing information and relevant evidence about the process of formation over time. The literature review was performed by means of bibliographical and documental analysis in books, theses, dissertations, specific journals on the subject, in addition to articles published on the Internet. The data were collected through informal conversations, semi-structured interviews and filming of the reports. The analysis was carried out from the phenomenological hermeneutic approach, which seeks to describe and interpret phenomena of human experience in order to investigate the essence through the identification of themes. The results point to the need for and possibility of expanding the use of TDIC as resource in the teaching and learning process, through training, dialogue, interaction, intentionality, expectations, hopes and their developments.